CURRENT ASPECTS OF COMPREHENSIVE DENTAL CARE FOR PATIENTS WITH DEFECTS OF THE MAXILLOFACIAL AREA - Sadriev Nizom Nazhmiddinovich; Lutfullayev Qobiljon; Musirmanov Abdusalim; Mutalifov Abduxalil; Norqulova Sevara (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Currently, the issues of surgical treatment of painful organs and tissues of the maxillofacial zone with defects and destructions remain an incompletely resolved problem. This is closely related to the increase in the number of patients with defects and deformations of the underside of the face due to non-gunshot and bullet injuries, ultimately osteomyelitis of the lower jaw and as a result of oncological effects. Having studied, analyzed the structure, diagnostic features, course, and methods of treatment of separate nosological configurations of tumors and tumor-like formations of the maxillofacial zone in children undergoing inpatient treatment in the department of maxillofacial surgery of the City Hospital for the period 2021. In the Department of Maxillofacial Surgery, a total of 948 children were cured, of which 5% of patients were cured from benign tumors, 81% from soft tissue tumors and 14% from benign tumors and tumor-like formations of the bones of the facial skeleton.